12 A Retrospective Study to Describe the Characteristics, Persistence and Adherence of Patients with Acute Coronary Syndromes (ACS) Prescribed Ticagrelor, Prasugrel or Clopidogrel in UK Primary Care. (6th June 2015) - Rigney, Una; Carder, Terence; Emmas, Cathy
Abstract : Background: NICE recommends that following ACS, patients are treated with dual antiplatelet therapy consisting of aspirin and an additional oral antiplatelet (OAP) for up to 12 months. There is evidence that early discontinuation of dual antiplatelet therapy increases risk of recurrent event and death. Objectives: To describe patient characteristics, persistence and adherence for patients prescribed OAP (clopidogrel, ticagrelor or prasugrel) in UK primary care following ACS. Methods: Retrospective cohort study in primary care data from Clinical Practice Research Datalink. The cohort consisted of patients prescribed OAP for first time (index date) between Dec-2010 and May-2014, with ACS event (myocardial infarction (MI), unstable angina or ACS unspecified) ≤ 3 months prior to index date and ≥ 12 months follow-up from index date. Persistence (Kaplan-Meier) was defined as days from index date to end of period covered by last prescription, with 30 day permissible gap. Patients were censored at earliest date of: transfer from practice, death, practice last collection. Adherence was defined as proportion of persistent period covered by medication (Medication Possession Ratio). Results: 9, 722 patients were prescribed OAP; 8, 589 (88.3%) clopidogrel, 752 (7.7%) prasugrel and 381 (3.9%) ticagrelor. The majority of patients were male (66.6%), this was more pronounced for ticagrelor (76.1%) and prasugrel (81.4%) compared to clopidogrel (64.8%). Compared to ticagrelor (mean age:62.5 years, SD:11.8) and prasugrel (mean age:58.9 years, SD:10.3), clopidogrel patients tended to be older (mean:68.8 years, SD:13.8). 37.7% of clopidogrel patients were ≥ 75 years vs 17.6% ticagrelor and 5.3% prasugrel. Overall, 89.7% had MI as index ACS event. Clopidogrel patients were more likely to have unstable angina as ACS event (3.7% vs 1.3% and 0.3% for ticagrelor and prasugrel). Clopidogrel patients were more likely to have co-morbidities, including cardiovascular disease other than ACS (62.7% vs 48.0% and 45.1% for ticagrelor and prasugrel), diabetes (20.9% vs 20.2 and 14.9% for ticagrelor and prasugrel) and renal disease (20.3% vs 9.5% and 7.3% for ticagrelor and prasugrel). Persistence, unadjusted for baseline characteristics, was similar for ticagrelor (mean:376.7, 95% CI:360.5–392.9, median:364) and prasugrel (mean:386.5, 95% CI:374.2–398.7, median:364). Mean persistence for clopidogrel was shorter: 339.7 days (95% CI:335.5–344.0, median:336). A quarter of clopidogrel patients discontinued therapy within 196 days of initiation compared to lower quartile of 336 days for ticagrelor and prasugrel. Adherence was high and similar across groups (≥ 96%). Conclusions: Clopidogrel patients tended to be older, more likely to be female, have unstable angina as index ACS event as well as history of cardiovascular diseases and co-morbidities. Persistence was similar in ticagrelor and prasugrel patients, and shorter for clopidogrel. Adherence to all antiplatelets was high.